Global environmental challenges - Speth, James Gustave (New Delhi, 2005)
This book will change the way we understand the future of our planet. It is both alarming and hopeful. James Gustave Spetch, renowned as a visionary environmentalist leader, warns that in spite of all the international negotiations and agreements of the past two decades, efforts to protect Earth's environment are not succeeding. Still, he says, the challenges are not insurmountable. He offers environmental threats around the world. The author explains why current approaches to critical global environmental problems Climate change, biodiversity loss, deterioration of marine environments, deforestation, water shortages, and others don't work now and won't work in the future. He provides a stinging critique of the failure of U.S. leadership and offers intriguing insights into why the U.S. has been able to address domestic environmental threats with some success while largely failing at the international level. Setting forth eight specific steps to a sustainable future, Speth convincingly argues that dramatically different and far-reaching actions by citizens and governments are now urgent. If ever a book could be described as essential, this is it.
Keywords: Environmental challenges